DECISION SUPPORT SYSTEM (DSS) DALAM PENGANGKATAN PELATIH PENCAK SILAT GERAK SAKA DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Aras Noto Nugroho; Hardiyan Hardiyan (Jurnal Techno Nusa Mandiri, 2016)
The crime rate in Indonesia is still very high, therefore martial will be very useful when there is something we do not want, Pencak silat gerak saka is one of the traditional martial arts that originated from Betawi and clean from the shirk. However, the limited number of trainers became an obstacle to its spread. With the decision support systems into a solution that provides support for consideration in the process of appointment of coaches who can be a standard reference in the process of appointment of the coach and facilitate the removal process to produce a new coach with the right to extend the deployment of the martial arts motion saka. In the research process using Analytic Hierarchy Process (AHP) where there are three criteria: character thought patterns and the sense that produces the appointment of the chairman as an important alternative.